The role of human capital and innovation capacity on economic growth in ASEAN-3 - Suriyani Muhamad,; Nor Fatimah Che Sulaiman,; Jumadil Saputra, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Human capital and innovation capacity are vital for driving economic growth. This study investigates the relationship between human capital and innovation capacity and its impact on economic growth in selected ASEAN countries, namely Malaysia, Indonesia, and Thailand. This study uses the Autoregressive Distributed Lag (ARDL) model through Bounds testing approach and the Error Correction Model (ECM) to examine the existence of long- and short-run relationships among variables. Human capital is proxied by tertiary enrolment (TER) and government expenditure on education (GEX). Meanwhile, the patent application (PTT) and high technology exports (HEX) reflect the innovation capacity. Using annual data for the periods from 1985 to 2015, the findings present substantial evidence for the existence of a long-run relationship between human capital and innovation capacity for the economic growth in Indonesia and Thailand. This study found that there is no long-run relationship between human capital and innovation capacity for the economic growth in Malaysia. The level of economic growth in Malaysia indicates that it has achieved the status of a medium to high-income nation. The policy implications suggest the need to strengthen the capability of ASEAN countries as ‘innovator’ countries instead of ‘user’ countries.